Mesenteric Panniculitis: An Enigma - Amit Kumar Gupta; Niraj Shrivastava (Iranian Journal of Medical Sciences, 2024)
Mesenteric panniculitis (MP) is one of the few rare chronic inflammatory disorders with an unknown etiology.